The response to thermospermine is fine-tuned by the balance between SAC51 and LHW family proteins in Arabidopsis thaliana - Xu, Yao; Saraumi, Mitsuru; Toyoshima, Tomohiko; Motose, Hiroyasu; Takahashi, Taku (Frontiers in Plant Science, 2025)
Thermospermine negatively regulates xylem formation. In Arabidopsis, SAC51 and SACL3, members of the SAC51 gene family encoding basic loop-helix-loop (bHLH) proteins play a key role in this regulation. These mRNAs contain an upstream open-reading-frame (uORF) that is highly conserved across species, and its inhibitory effect on the main ORF translation is alleviated by thermospermine. A double knockout of SAC51 and SACL3 results in thermospermine insensitivity at high concentrations that normally inhibit xylem formation and shoot growth in the wild type. Conversely, uORF mutants of SAC51, SACL3, and SACL1 suppress the excessive xylem formation and dwarf phenotype of acl5, a mutant defective in thermospermine biosynthesis. In this study, we generated genome-edited uORF mutants of SACL2 and confirmed that they partially recover the acl5 phenotype. All uORF mutants exhibited increased sensitivity to thermospermine. SACL3 represses the function of LHW, a key bHLH transcription factor required for xylem proliferation, through direct interaction. We found that the lhw mutant is also hypersensitive to thermospermine, while this sensitivity was suppressed by the sac51 sacl3 double knockout. Yeast two-hybrid assays demonstrated that all four SAC51 family members interact with LHW and its family members. These findings suggest that overaccumulation of SAC51 family proteins leads to thermospermine hypersensitivity by repressing the function of LHW family proteins, whose activity must be fine-tuned to ensure proper xylem development.